Pengaruh Hubungan Pola Makan terhadap Kadar Gula Darah Pasien Diabetes Mellitus Tipe II - Siti Nur Istiqomah; Mally Ghinan Sholih (Jurnal Sehat Mandiri, 2024)
Diabetes Mellitus is a metabolic disorder that affects the processing of carbohydrates, proteins and fats in the body, characterized by hyperglycemia, or increased blood glucose levels. The main cause of hyperglycemia is an abnormality in the production or secretion of insulin, the hormone that regulates blood glucose. Irregular eating patterns increase the risk of DM, so it is important for DM sufferers to control their eating patterns. This study aims to determine the influence of diet on blood sugar levels in type II Diabetes Mellitus patients. The research method used was to conduct a literature study in several journals with journal criteria for the last 10 years, namely from publication year 2014 to 2024. The results obtained were 14 journals showing the influence of the relationship between diet and blood glucose levels, this was stated as a value. The p-value is smaller than 0.05, and 1 journal concluded that there was no influence between diet and blood sugar levels with a p-value of 0.056 which was greater than 0.05. Conclusion: Irregular eating patterns are a factor that plays a major role in the incidence of Diabetes Mellitus, the more irregular the eating pattern, the more likely a person is to experience Diabetes Mellitus. Suggestion: It is important to regulate the amount, type and time of food consumed to control blood glucose levels.